Myricetin Alleviates Pathological Cardiac Hypertrophy via TRAF6/TAK1/MAPK and Nrf2 Signaling Pathway. (6th December 2019) - Liao, Hai-han; Zhang, Nan; Meng, Yan-yan; Feng, Hong; Yang, Jing-jing; Li, Wen-jin; Chen, Si; Wu, Hai-ming; Deng, Wei; Tang, Qi-zhu
Abstract : Myricetin (Myr) is a common plant-derived polyphenol and is well recognized for its multiple activities including antioxidant, anti-inflammation, anticancer, and antidiabetes. Our previous studies indicated that Myr protected mouse heart from lipopolysaccharide and streptozocin-induced injuries. However, it remained to be unclear whether Myr could prevent mouse heart from pressure overload-induced pathological hypertrophy. Wild type (WT) and cardiac Nrf2 knockdown (Nrf2-KD) mice were subjected to aortic banding (AB) surgery and then administered with Myr (200 mg/kg/d) for 6 weeks. Myr significantly alleviated AB-induced cardiac hypertrophy, fibrosis, and cardiac dysfunction in both WT and Nrf2-KD mice. Myr also inhibited phenylephrine- (PE-) induced neonatal rat cardiomyocyte (NRCM) hypertrophy and hypertrophic markers' expression in vitro . Mechanically, Myr markedly increased Nrf2 activity, decreased NF- κ B activity, and inhibited TAK1/p38/JNK1/2 MAPK signaling in WT mouse hearts. We further demonstrated that Myr could inhibit TAK1/p38/JNK1/2 signaling via inhibiting Traf6 ubiquitination and its interaction with TAK1 after Nrf2 knockdown in NRCM. These results strongly suggested that Myr could attenuate pressure overload-induced pathological hypertrophy in vivo and PE-induced NRCM hypertrophy via enhancing Nrf2 activity and inhibiting TAK1/P38/JNK1/2 phosphorylation by regulating Traf6 ubiquitination. Thus, Myr might be a potential strategy for therapy or adjuvant therapy for malignant cardiac hypertrophy.